Utilising distributed acoustic sensing for monitoring rock mass stress conditions in underground mining: a case study - Dande, S; Forbes, E; Butler, T; Graham, K; Hawryluck, C; Hall, A; Simser, B; Chauvet, R; Cherubini, A (Deep Mining 2024: Proceedings of the 10th International Conference on Deep and High Stress Mining, 2024)
Distributed fibre optic sensing (DFOS) technology is widely employed in the oil and gas industry for monitoring seismicity, strain and temperature during hydraulic fracturing of unconventional reservoirs. However, it is only in the early stages of application in the mining industry. This paper presents a case study on the application of distributed acoustic sensing (DAS) technology to monitor rock mass stress conditions in an underground mine. The objective of this pilot project was to assess the viability of, and challenges associated with, installing fibre optics and their effectiveness in monitoring rock mass response to mining activities. An engineered fibre optic cable was deployed and grouted in a 200 m-deep borehole to monitor seismicity and strain. The raw DAS strain rate data were divided into two frequency bands: a high-frequency band (above 10 Hz) for microseismic processing and a 1–10 Hz frequency band for strain processing. Microseismic events and blasts detected by the fibre were co-located with existing geophones and accelerometers to enhance event location accuracy and precision. While the existing network of geophones provided accurate event locations, the addition of DAS increased the precision of these measurements. In addition to microseismic monitoring, the energy attribute within the 1–10 Hz band of DAS strain rate data was analysed. This analysis revealed a clear correlation between elevated energy levels on the fibre during raisebore operations and a levelling off after the completion of raiseboring. The observed intermittent high and low energy levels on the fibre could be used for safety assessments during raisebore operations as these energy fluctuations reflect the impact of raisebore activities on rock mass stress. Based on this limited dataset, DAS technology has the potential to offer valuable insights into rock mass behaviour in underground mining environments by monitoring stress and strain conditions during operations such as raiseboring, development and production blasts. When combined with existing seismic systems, DAS provides an additional data point for enhancing hazard mitigation strategies in underground mining operations.
Keywords: fibre optics; distributed acoustic sensing; seismicity; rock mass creep monitoring; mining; geophones; data integration; raisebore